2003
DOI: 10.1152/ajpheart.01116.2002
|View full text |Cite
|
Sign up to set email alerts
|

Endopeptidases 3.4.24.15 and 24.16 in endothelial cells: potential role in vasoactive peptide metabolism

Abstract: Endopeptidase activity was assessed using a specific quenched fluorescent substrate [7-methoxycoumarin-4-acetyl-Pro-Leu-Gly-D-Lys(2,4-dinitrophenyl)], as well as the peptide substrates bradykinin and neurotensin (assessed by high-performance liquid chromatography with mass spectroscopic detection). Our results indicate that both peptidases are present in endothelial cells; however, EP24.16 contributes significantly more to substrate cleavage by both cytosolic and membrane preparations, as well as intact cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…[7][8][9][10]13 Several studies have detailed the effects of cyclic strain on secretory processes in vascular cells. Given the regulatory influence of cyclic strain on soluble levels of EP24.15 and EP24.16 activity described here, it was decided to examine its potential influence on endopeptidase release from BAECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10]13 Several studies have detailed the effects of cyclic strain on secretory processes in vascular cells. Given the regulatory influence of cyclic strain on soluble levels of EP24.15 and EP24.16 activity described here, it was decided to examine its potential influence on endopeptidase release from BAECs.…”
Section: Discussionmentioning
confidence: 99%
“…6 Sitedirected inhibitors of both enzymes have been shown to potentiate bradykinin-induced vasodilation 11 and to decrease myocardial ischemia/reperfusion injury. 12 More recent studies by Norman et al 13,14 and Rioli et al 15 16,17 These cumulative observations clearly point to a physiological role for these related enzymes in regulating the balance between pressor and depressor peptides within the vasculature, thereby contributing significantly to the maintenance of vascular tone and homeostatic mechanisms.…”
mentioning
confidence: 98%
“…It has been previously suggested that in vivo Nln contributes to the metabolism of several endogenous peptides including neurotensin, bradykinin, angiotensins, substance P, opioids (i.e. metorphamide, dynorphin A 1-8 ), somatostatin, and hemopressin (5,10,26,80). The presence of Nln activity in vascular endothelial cells suggested a possible physiological role for Nln in blood pressure control (79).…”
Section: Ms Spectramentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) were maintained in Dulbecco's modified Eagle's medium supplemented with 8% (v/v) fetal bovine serum, 1% penicillin/streptomycin/glutamine and HAT supplement (1 vial/500 mL of media; Sigma), as mentioned previously [15].…”
Section: Cell Culturementioning
confidence: 99%